Relationship Between Physical Disability, Disease Activity and Osteoporosis in Patients With Rheumatoid Arthritis
Objectives: This study aims to assess the relationship between the physical disability, degree of disease activity, and bone mineral density in menopause patients diagnosed with rheumatoid arthritis (RA). Patients and methods: The study included 130 females (mean age 62.77Å